Victims and/or perpetrators? Towards an interdisciplinary dialogue on child soldiers. Issue 1 (December 2015) - Derluyn, Ilse; Vandenhole, Wouter; Parmentier, Stephan; Mels, Cindy
Abstract Background Worldwide, thousands of children are acting in different roles in armed groups. Whereas human rights activism and humanitarian imperatives tend to emphasize the image of child soldiers as incapable victims of adults' abusive compulsion, this image does not fully correspond with prevailing pedagogical and jurisprudential discourses, nor does it represent all child soldiers' own perceptions of their role. Moreover, contemporary warfare is often marked by fuzzy distinctions between perpetrators and victims. This article deepens on the question how to conceptualize the victim-perpetrator imaginary about child soldiers, starting from three disciplines, children's rights law, psychosocial approaches and transitional justice, and then proceeding into an interdisciplinary approach. Discussion We argue that the victim–perpetrator dichotomy in relation to child soldiers needs to be revisited, and that this can only be done successfully through a truly interdisciplinary approach. Key to this interdisciplinary dialogue is the growing awareness within all three disciplines, but admittedly only marginally within children's rights law, that only by moving beyond the binary distinction between victim- and perpetrator-hood, the complexity of childhood soldiering can be grasped. In transitional justice, the concept of role reversal has been instructive, and in psychosocial studies, emphasis has been put on the 'agency' of (former) child soldiers, whereby child soldiers sometimes account on how joining the armed force or group was (partially) out of their own free will. Hence, child soldiers' perpetrator-hood is not only part of the way child soldiers are perceived in the communities they return to, but equally of the way they see themselves. These findings plea for more contextualized approaches, including a greater participation of child soldiers, the elaboration of accountability mechanisms beyond criminal responsibility, and an intimate connection between individual, social and societal healing by paying more attention to reconciliation. Summary This article deepens on the question how to conceptualize the victim-perpetrator imaginary about child soldiers through an interdisciplinary dialogue between children's rights law, psychosocial approaches and transitional justice. With this interdisciplinary perspective, we intend to open up narrow disciplinary viewpoints, and contribute to more integrated approaches, beyond a binary distinction between victimhood and perpetrator-hood.